Pengembangan E-LKPD Menggunakan Website Wizer.me Pada Materi Pengaruh Gaya Terhadap Benda - Firli Pitriyani; Teti Rostikawati; Dendy Saeful Zen (STKIP Subang, 2025)
This study aims to develop an E-LKPD using the website wizer.me, as well as to determine the feasibility and effectiveness of the E-LKPD. The methodology used in this study is research and development with the ADDE development model at SDN Puspanegara 08. The research subjects were 4th grade student totaling 27 students. The research was conducted in the second semester of the 2024/2025 academic year. In this study, validation tests were conducted on the E-LKPD product by medi experts, language experts, and subject matter experts. The validation result from the media expert obtained 100% with a “very feasible” criterion, the language expert obtained 100% with a “very feasible” criterion, and the subject matter expert obtained 92% with a “very feasible” criterion. The result of the students response questionnaire showed 90% with a “very good” category, and the average N-Gain score was 0,71, which falls into the “high” category. The result of the study indicate that the use of E-LKPD via the wizer.me website is highly effective in supporting the learning process and has proven to improve student learning outcomes.